Non-urban international passenger transport (Transport outlook)
This database contains the full outputs from the analysis, which is also updated every other year in line with the publication. It covers the travel demand, vehicle activities, energy consumption, as well as related CO2 emissions of all modes (existing and new emerging modes) for both freight (urban, non-urban, and international) and passenger transport (urban, non-urban, and international), under three different policy scenario (Recovery, Reshape, and Reshape+)